2002
DOI: 10.3758/bf03196308
|View full text |Cite
|
Sign up to set email alerts
|

The crucial roles of stimulus matching and stimulus identity in negative priming

Abstract: Negative priming refers to the situation in which an ignored item on an initial prime trial suffers slowed responding when it becomes the target item on a subsequent probe trial. In this experiment (and a replication), we demonstrate two ways in which stimulus consistency (matching) governs negative priming. First, negative priming for identical words occurred only when the prime distractor changed color when it became the probe target (i.e., constant cue to read the red word); negative priming disappeared whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
6
29
1
1
Order By: Relevance
“…No reliable negative priming effects were observed on repeated same-location trials. These results are consistent with demonstrations in the visual domain, revealing that some instances of negative priming may be explained entirely by a mismatch in the features of a repeated stimulus (e.g., MacLeod et al, 2002). Also, our findings raise the possibility that mismatches on other auditory dimensions, such as loudness or pitch, may also give rise to negative priming effects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…No reliable negative priming effects were observed on repeated same-location trials. These results are consistent with demonstrations in the visual domain, revealing that some instances of negative priming may be explained entirely by a mismatch in the features of a repeated stimulus (e.g., MacLeod et al, 2002). Also, our findings raise the possibility that mismatches on other auditory dimensions, such as loudness or pitch, may also give rise to negative priming effects.…”
Section: Discussionsupporting
confidence: 81%
“…The results of several experiments have shown that this type of mismatching can produce negative priming effects (Lowe, 1985;MacDonald & Joordens, 2000;MacDonald, Joordens, & Seergobin, 1999;MacLeod, Chiappe, & Fox, 2002;Park & Kanwisher, 1994;Milliken, Tipper, & Weaver, 1994). Demonstrations that such mismatches may impair responding to previously attended stimuli provide particularly convincing support for this approach.…”
Section: Feature Mismatch Approaches To Negative Primingmentioning
confidence: 77%
“…By contrast, in visual NP tasks, the target stimuli have most commonly been identified by color, with the target color remaining constant throughout the experiment (or at least throughout a block of trials). One study even found diminished NP effects when the target color changed between prime and probe displays (see MacLeod, Chiappe, & Fox, 2002). In the present study, we varied the feature that specified the target vibration (i.e., the display color indicating the target hand) unpredictably from trial to trial.…”
Section: Discussionmentioning
confidence: 99%
“…These semantic NP effects are usually smaller than effects obtained from identity or spatial tasks (Fox, 1995) and a sizeable portion of studies also report a failure to replicate semantic NP. This has led to a debate in the last few years concerning whether semantic NP actually exists (Chiappe & MacLeod, 1995;MacLeod, Chiappe, & Fox, 2002).…”
Section: Np Task (Basics)mentioning
confidence: 99%